Application of carbon-based catalysts derived from compost on catalytic wet peroxide oxidation of leachate waters from mechanical and biological treatment plant units for municipal solid waste - Batista, Gabriel de Freitas (2021)
This work aims at the valorization of compost from mechanical and biological treatment (MBT) units of municipal solid waste by their transformation into carbon-based catalysts for further application in the treatment of MBT leachate waters (chemical oxygen demand (COD) = 60.0 g L-1, total organic carbon (TOC) = 26.7 g L-1, five-day biochemical oxygen demand (BOD5) = 23.3 g L-1 and aromaticity = 10.2 g L-1). The catalyst was prepared in this work by hydrothermal carbonization at 230 ºC from compost obtained in a MBT unit. The treatment of the leachate waters was conducted by combining a pre-treatment with a cationic ion exchange resin followed by catalytic wet peroxide oxidation (CWPO). The CWPO step was operated for 24 h using 7.2 g L-1 of catalyst, 85.7 g L-1 of H2O2 poured inside the reactor in 5 stepwise additions, at 80 ºC and pH = 3. The combined treatment by cationic resin and CWPO led to obtain removals of 68.2, 65.4, 96.8 and 93.1 % for COD, TOC, BOD5 and aromaticity, respectively, after 24 h of reaction. In conclusion, it was found that compost is a suitable precursor to produce active catalysts for the CWPO of leachate waters.